Brea gum as wall material in the microencapsulation of corn oil by spray drying: Effect of inulin addition - Castel, María Virginia (2018)
This study aimed to evaluate the potential of Brea gum (BG) in the microencapsulation of corn oil in comparison with gum arabic (GA) and evaluate the effect of adding inulin at the matrix formulation. Different concentration of BG and inulin were used to emulsify pure corn oil using a homogenizer followed by an ultrasonic treatment. Then, emulsions were spray dried in laboratory scale equipment to obtain the microcapsules. Overall, powders presented spherical shape with surface concavities, no apparent cracks and high polydispersity. However, some powders containing inulin showed particles that seem to have fused together reflecting a coating effect of inulin. Moisture content of BG powders were low but increased with inulin addition, while water activities (˂0.4) were not affected by inulin. The color analysis showed that BG powders presented lower luminosity and higher red and yellow parameters than GA powder, and adding inulin decreased the lightness, redness and yellowness resulting in powders with more pale color. Encapsulation efficiency increased with BG concentration, reaching 76.12% with 20% of BG. Further efficiency improvement was achieved in presence of inulin, reaching the highest value (91.72) with 20% BG/20% inulin formulation, which was higher than the efficiency achieved with GA (88.66%). It was concluded that the combination of BG and inulin could be used as an alternative wall material for microencapsulation of hydrophobic compounds in replacement of GA.